The Collective Impact Index (CII): A New Instrument to Evaluate and Foster Collaborative Partnership in Public Health practice - Hamisu M Salihu, MD, PhD; Roneé E Wilson, PhD, MPH; Estrellita "Lo" Berry, MA (Global Health and Education Projects, Inc., 2018)
Background or Objectives: Collective Impact (CI) is the sum of collaborative actions through coalition building to examine and address issues that threaten public health. We sought to develop an instrument to measure CI across diverse health-related organizations. Methods: The study was performed in 5 phases initiated with a comprehensive literature review through the generation of candidate items using a deductive instrument development approach. A matrix was then created to map assembled items onto related CI domains. An one-hundred and nine (n=109) item questionnaire covering multiple items per domain was administered to 200 health-related organizations selected randomly throughout the United States. Survey data were evaluated using Principal Component Analysis and Kaiser criterion or eigenvalue-greater-than-one rule was the factor retention method utilized. Results: Based on Kaiser's eigenvalue criteria and communality estimates, the number of items across the five domains of CI was reduced from 109 to 20, with 4 items populating each subdomain. All communality estimates in the final instrument had values > 0.6, which was sufficiently adequate as per Kaiser's criterion. Conclusion and Global Health Implications: This pilot study demonstrates CI represents a multifactorial concept with domains that are multi-dimensional capturing diverse aspects of a construct. We developed the first measure of CI for public health practice. The index bears potential utility for assessing and monitoring areas of strengths and weaknesses within collaborative partnerships across the spectrum of population health. Key words: Collaborative Partnerships. CI. Federal Healthy Start. Program Evaluation. Index. Public Health Practice Copyright © 2018 Salihu et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.